Empowering stroke survivors beyond inpatient rehabilitation: the STRIDE program - Cassidy, Jessica M.; Fitzgerald, Ryan; Vaughn, Rachel M.; Geib, Anna; Marquie, Maureen; Trei, Anna Claire; Morrison, Blaise; Lewek, Michael D.; Baratta, John M. (Frontiers in Stroke, 2023)
The timeframe from hospital discharge to the commencement of outpatient therapies represents a crucial yet often overlooked period in post-stroke recovery. We designed an eight-week post-stroke management program (STRIDE, Stroke Management Training and Inpatient Rehabilitation Discharge Education) targeting individuals discharging from an inpatient rehabilitation facility to home. The primary aims of this pilot study were to determine STRIDE feasibility and participant engagement. Participants with first or recurrent stroke were enrolled. Each week, participants monitored and recorded their daily activity, completed a 15-minute educational module and quiz, and partook in weekly and biweekly communication with a fellow participant and STRIDE coordinator, respectively. Feasibility was evaluated by successful initiation of STRIDE and enrollment of the target population. We also assessed participant adherence and conducted semi-structured exit interviews. Of the 99 individuals screened, 20 individuals were enrolled (7 females, 28.6 ± 15.7 days post-stroke). Several participants were unable to begin the program (n=6) or complete the program (n=4). Overall, participants completing at least 1 week of STRIDE (n=14) demonstrated adherence with education module and quiz completion and communication with the STRIDE coordinator. Participant feedback from interviews was largely positive, underscoring the value of STRIDE during early poststroke recovery. These findings support the feasibility of an initiated multi-faceted stroke management program. Participant dropout was a limitation and serves as a consideration when designing future iterations of STRIDE. With the long-term goal of promoting autonomy and investment in one's continued recovery beyond the inpatient setting, STRIDE bridges the transition from hospital to home.